Birth Defects in the Newborn Population: Race and Ethnicity - Alexander C. Egbe (Elsevier, 2015)
Racial variability in certain prenatal risk factors, such as prenatal vitamin supplementation and termination of pregnancy for fetal anomaly, has altered the racial prevalence of birth defects. Analysis of a single large representative population is required to analyze current racial differences in the prevalence of birth defects in the United States. Methods: This is a population-based cross-sectional study to analyze racial differences in the prevalence of birth defects. We reviewed all live births in the 2008 Nationwide Inpatient Sample (NIS) database and determined birth prevalence of 55 selected birth defects in Caucasians. We then calculated the relative risk of these birth defects in African-Americans, Hispanics, and Asians relative to Caucasians. Result: Overall birth defect prevalence was 29.2 per 1000 in a cohort of 1,048,252 live births, of which 51% were Caucasians. Compared with Caucasians, the risk of overall birth defects was lower in African-Americans (relative risk = 0.9, confidence interval 0.8-0.9) and Hispanics (relative risk = 0.9, confidence interval 0.8-0.9). The risk of overall birth defects was similar in Caucasians and Asians. Relative to the Caucasians, African-Americans had a lower risk of cardiac, genitourinary, and craniofacial malformations but a higher risk of musculoskeletal malformations. Hispanics had a lower risk of genitourinary and gastrointestinal malformation. Asians had a higher risk of craniofacial and musculoskeletal malformations. Conclusion: This is a comprehensive description of racial differences in the risk of birth defects in the United States. Observed racial differences in the risk of birth defects may be related to genetic susceptibilities, to cultural or social differences that could modify exposures, or to the many potential combinations between susceptibilities and exposures.